Hyperfocusing as a dimension of adult attention deficit hyperactivity disorder. (December 2016) - Ozel-Kizil, Erguvan Tugba; Kokurcan, Ahmet; Aksoy, Umut Mert; Kanat, Bilgen Bicer; Sakarya, Direnc; Bastug, Gulbahar; Colak, Burcin; Altunoz, Umut; Kirici, Sevinc; Demirbas, Hatice; Oncu, Bedriye
Abstract: Patients with Attention Deficit Hyperactivity Disorder (ADHD) suffer not only from inability to focus but also from inability to shift attention for events that trigger their interests. This phenomenon is called "hyperfocusing". Previous literature about hyperfocusing is scarce and relies mainly on case reports. The study aimed to investigate and compare the severity of hyperfocusing in adult ADHD with and without psycho-stimulant use. ADHD (DSM-IV-TR) patients either psycho-stimulant naive (n = 53) or on psycho-stimulants (n = 79) from two ADHD clinics were recruited. The control group (n = 65) consisted of healthy university students. A socio-demographic form, the Beck Depression Inventory, the Wender-Utah Rating Scale, the Adult ADHD Self- Report Scale and the Hyperfocusing Scale were applied to the participants. There was no difference between total Hyperfocusing Scale and Adult ADHD Self- Report Scale scores of two patient groups, but both have higher scores than controls (p < 0.001). Hyperfocusing is higher in adult ADHD and there was no difference between stimulant-naive patients or patients on stimulants. Hyperfocusing can be defined as a separate dimension of adult ADHD.